JC virus-induced progressive multifocal leukoencephalopathy in a presumably healthy patient - Xiang Wang; Jinxiu Chen; Jing Gong; Ying Wu; Xiang-hao Liu (BMC Neurology, 2022)
Abstract Background JC virus (JCV) is common among healthy individuals and remains latent but may be reactivated under immunosuppressive conditions, resulting in progressive multifocal leukoencephalopathy (PML). Here, we present a rare case of PML caused by JC virus infection in a previously healthy and immunocompetent patient. Case presentation A 67-year-old female without any disease history was admitted after presenting with rapidly progressive dementia. The preoperative diagnosis was progressive multifocal leukoencephalopathy, and corticosteroid treatment did not improve the symptoms. Brain lesions were surgically sampled, and JCV infection was confirmed by high-throughput DNA gene detection. This patient received a combined treatment of mirtazapine, mefloquine, and traditional Chinese herbs, and had stabilization of the disease on followed-up. Conclusions Although it is a rare, this case demonstrates that JC virus infection within the brain occurs in apparently healthy people. This case may increase our understanding of virus infection when facing the coronavirus epidemic in recent years, considering that similar medications were used. Graphical Abstract